2012
DOI: 10.3928/15428877-20120802-02
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Subconjunctival Bevacizumab as an Adjunctive Treatment in Primary Pterygium: A Preliminary Report

Abstract: Intraoperative subconjunctival bevacizumab following primary pterygium surgical excision is not helpful and possibly harmful. Larger studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 37 publications
0
11
1
2
Order By: Relevance
“…In contrast to our study and most of the previous studies on the use of bivacizumab in pterygium surgery, Maha et al31 and Mohamed et al32 found that a subconjunctival injection of 1.25 mg/0.05 mL of bevacizumab at the end of the surgery did not result in a statistically significant difference in the recurrence rates or postoperative conjunctival erythema with discomfort, lacrimation, photophobia, or healing of corneal epithelial defects after pterygium excision.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our study and most of the previous studies on the use of bivacizumab in pterygium surgery, Maha et al31 and Mohamed et al32 found that a subconjunctival injection of 1.25 mg/0.05 mL of bevacizumab at the end of the surgery did not result in a statistically significant difference in the recurrence rates or postoperative conjunctival erythema with discomfort, lacrimation, photophobia, or healing of corneal epithelial defects after pterygium excision.…”
Section: Discussioncontrasting
confidence: 99%
“…In the series by Shahin et al. (), two cases developed conjunctival autograft pallor 1 week following intra‐operative subconjunctival bevacizumab injection. One led to early recurrence, and the other led to a graft loss.…”
Section: Resultsmentioning
confidence: 99%
“…Shahin et al. () studied subconjunctival bevacizumab after conjunctivo‐limbal autograft and found the bevacizumab group had a higher recurrence rate compared to the control group (20% versus 9.5% respectively). In addition, the recurrence in the bevacizumab group occurred earlier and more aggressively, including two cases that exhibited conjunctivo‐limbal graft pallor and subsequent failure.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the favorable effect was incomplete and temporary, similar to that reported by Leippi et al (25) . Previous reports suggesting the effective role of subconjunctival bevacizumab were noncomparative case reports (25,28,31) . Corneal neo vascularization was inhibited or regressed, but not completely elimi …”
Section: Discussionmentioning
confidence: 99%